Optimization of saponins, phenolics, and antioxidants extracted from fenugreek seeds using microwave-assisted extraction and response surface methodology as an optimizing tool - Akbari, Sweeta; Nour, A. H.; R. M., Yunus (Elsevier Masson SAS, 2019)
Fenugreek is a multiregional plant mostly found in Asia, the Middle East, and some European countries. Thus, this study aimed to optimize the microwave-assisted extraction (MAE) process parameters such as irradiation time (2–4 min), ethanol concentration (40–80%), microwave power (500–700 W), solid-to-liquid ratio (1:8–1:12 g/mL), and a fixed extraction temperature (70 °C) for fenugreek seed powder. Response surface methodology (RSM) was applied to optimize MAE process parameters to achieve optimal total saponin content (TSC), total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), and 2,2′-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) antioxidant capacities of fenugreek seed extract. The levels of independent variables were first evaluated using one-factor-at-one-time method, after which the suitable levels (−1, 0, and +1) were selected for the optimization process. The optimal conditions of MAE parameters were found to be 2.84 min, 572.50 W, 63.68%, and 0.09 g/mL. Based on the suggested optimum conditions, the obtained responses were 195.89 ± 1.07 (mg diosgenin equivalent/g d.w.), 81.85 ± 0.61 (mg gallic acid equivalent/g d.w.), 92.86 ± 0.56%, and 95.85 ± 0.81%. Analysis of variance revealed that all the responses including TSC, TPC, DPPH, and ABTS antioxidant capacities were significantly influenced (P < 0.05) by irradiation time, solvent concentration, microwave oven power, and feed-to-solvent ratio. Hence, the results obtained from liquid chromatography–quadrupole–time-of-flight mass spectrometry indicated the presence of steroid saponins, triterpenoid saponins, phenolics, and other natural antioxidants.